Web based collaborative microtexts creation theoretical foundations: Eseeusee model. - Antón Cuadrado, Raúl; Valverde Velasco, Alicia (Historia y Comunicación Social, 2014)
The digital technologies have facilitated the development of a horizontal communication in which all the participants could have identical competence in the creation. In this sense, the model Eseeusee generates an on line agora that gives content to this type of communication and that provides a space for the creation of microtexts in a collaborative way.
Keywords: Cocreation; Horizontal communication; Authorship; Microtexts; Rewriting; Coauthorship.